Analysis Of Behavior The Eradication Of Family Mosquito Nest With Larva Mosquito Free Number - Suci Pratiwi (Chakra Brahmanda Lentera Institute, 2019)
Many people are still not aware of the cleanliness of the environment and the slow pace of the government in anticipating and responding to the spread of dengue cases. The aim of the study was to have a relationship between the behavior of eradicating mosquito nests and larvae in Paleleh Village, Paleleh District, Buol District, Central Sulawesi Province. The design used in the study was cross sectional. Population is all families. The sample size was 168 respondents using Purposive Sampling techniques. Independent variable research is behavior. The dependent variable is the larva mosquito free number. Data was collected using a questionnaire, then the data were analyzed using the Spearman Rho test, with a significance level of α ≤ 0.05. The results showed that most respondents had sufficient mosquito nest eradication behavior as many as 106 respondents (63.1%), free larvae as many as 138 respondents (82.1%), statistical test results obtained p = 0,000 with a = 0.05, there is a significant relationship in the variable of eradicating mosquito nest behavior in the presence of larvae, with a correlation coefficient of 0.773 which means having a strong relationship. Flicking eradication behavior has an impact on the existence of larvae in the family so that sufficient behavior needs to be continuously improved in order to be good.